Ephesian women in Greco-Roman and early Christian perspective - Karaman, Elif Hilal 1985- (Tübingen Mohr Siebeck, 2018)
Cover -- Titel -- Preface -- Table of Contents -- Table of Figures -- Chapter 1: Introduction -- A. Place and Time -- B. Sources and Analytical Categories -- I. Early Christian Writings -- II. Analytical Categories -- III. Ephesian Greco-Roman Literary and Archaeological Evidence -- IV. The "Women" in our Sources -- C. Method -- D. Terminology -- Chapter 2: History of Scholarship -- A. The Location: Ephesus -- I. The Locality Argument -- B. The Subject: Women -- C. Outline of Chapters -- Chapter 3: Social History of Ephesus -- A. Ancient History of the City -- B. The Principate -- I. The Legal Situation in Ephesus -- C. The Temple of Artemis and Imperial Cult Temples -- D. Domestic Life -- E. Conclusion -- Chapter 4: Marriage -- A. Who Makes Up a Household? -- I. What is in the sources? -- B. The Perception of Marriage in Ephesus -- I. Inside the Home -- II. Epigraphic Evidence -- III. Marriage in Greco-Roman Society -- 1. Age of Marriage -- 2. Education of Girls -- 3. Dowry -- 4. The Wedding -- 5. The Legal Part of Marriage -- a. Marriage and Guardianship -- b. Ius Trium Liberorum -- IV. Conclusion -- C. The Perception of Marriage in Early Christian Ephesian Writings -- I. The Authorship Argument -- II. Christian, Greco-Roman, or Both? -- 1. Attitudes Towards the Christianisation of Greco-Roman Customs -- 2. Motivation Behind Christianisation of Greco-Roman Customs -- 3. Should They Divorce the Unbelieving Spouse? -- III. Equal or Superior? -- IV. Bishops' Opinions on Wives -- D. Conclusion -- Chapter 5: Widows and Other Single Women -- A. Why Widows, Virgins and Divorcees? -- B. Ephesian Widows, Virgins and Divorcees -- I. Epigraphic Evidence -- 1. Widows and Divorcees -- 2. Virgins -- II. Reputation of Widows -- 1. Petronius' 'Widow of Ephesus' -- 2. Melite of Ephesus -- III. Widows in Greco-Roman Society -- 1. The Issue of Remarriage
2. In Old Age -- IV. Conclusion -- C. Widows and Other Single Women in the Early Christian Ephesian Writings -- I. The Issue of Remarriage -- II. 'Real Widows' and 'So-called Widows' -- III. Bishops' Opinions on Widows -- D. Conclusion -- Chapter 6: Women in Social Life -- A. The Limits of Social Life -- B. Women in Social Life in Ephesus -- I. The Appearance of Women in Ephesus -- 1. Women's Head Coverings -- 2. Men's Head Coverings -- 3. Women's Apparel -- II. The Roles of the Women in Society in Ephesus -- III. Conclusion -- C. The Social Life of Women in Early Christian Ephesian Writings -- I. Named Women Connected with Asia Minor -- 1. Prisca and Aquila/Aquila and Priscilla -- II. Head Coverings in Early Christianity -- III. Women's Apparel in Early Christianity -- D. Conclusion -- Chapter 7: Teachers -- A. Why Teachers? -- B. Teachers in Greco-Roman Society -- C. 'Teaching' in the Early Christian Ephesian Writings -- D. Conclusion -- Chapter 8: Conclusion -- Bibliography -- Indexes -- Index of Subjects, Names and Places -- Index of References -- Index of Modern Authors
Keywords: Hochschulschrift